Early overpressuring in organic-rich shales during burial: evidence from fibrous calcite veins in the Lower Jurassic Shales-with-Beef Member in the Wessex Basin, UK - Meng, Q; Hooker, J; Cartwright, J (Geological Society, 2017)
Field, petrographic and geochemical analysis of fibrous calcite veins in the Lower Jurassic Shales-with-Beef Member in the Wessex Basin was conducted to investigate the formation mechanism of the veins. Bedding-parallel fibrous calcite veins, including beef veins and tabular cone-in-cone structures, are widespread in the black shales. The calcite veins consist of subvertical fibrous crystals and a dark median zone. The median zone contains scattered clays, pyrite microcrystals, skeletal fragments and amorphous organic matter. The veins exhibit moderate carbon isotope values, ranging from -1.515 to 2.732‰. The oxygen isotope composition ranges from -8.872 to -4.521‰, which is possibly too negative to reflect the primary porewater oxygen isotope signatures and indic ates a porewater modification. It is interpreted that the veins mainly derive carbonates from seawater inorganic carbon and bioclasts. The veins formed as closed-system hydraulic fractures in overpressured cells during sediment degassing in the methanogenic zone. The shale beds with a high total organic carbon content could have generated abundant CO 2 , which may have resulted in either the cementing of the pores in the matrix or overpressure buildup. The skeletal fragments provide a control on the spatial distribution of veins as nuclei for calcite precipitation from supersaturated pore fluids.